Assessment of Salt Water Upconing to above Groundwater Abstraction Facilities - Hoang, Nguyen Van; Hung, Vu Dinh; Cong, Nguyen Thanh (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1DO - 10.25073/2588-1094/vnuees.4228, 2018)
Abstract: A methodology for identifying salt water upconing to groundwater abstraction wells has been based on Dagan and Bear method for an abstraction point. The results of the analysis for different design cases of well field and screen length and positions for coastal sand dune aquifer in Thach Ha district, Ha Tinh province has showed that the height of salt water upconing is inversely proportional to the distance from the well screen bottom to the salt and fresh water interface. At the same time, for abstraction wells with the same depth, the height of salt water upconing as well as the time of salt water upconing to the abstraction wells are inversely proportional to the length of the well screen (i.e. the longer the well screen the less salt water upconing). The use of several abstraction wells to reduce the abstraction rate of each well (the total abstraction rate remains unchanged) has the effect of significantly reducing the salt water upconing process. The proposed methodology for salt water upconing assessment has been shown an effective role in supporting the design of groundwater abstraction facilities that are at risk of salinization from the lower part or lower aquifers for sustainable groundwater exploitation on the viewpoint of ensuring the quality of abstracted water and of protecting groundwater resources by limiting (even preventing) salt water intrusion.